Assessing the Operation Management: A Case of Narayani Lift Irrigation System, Nepal - Ruwali, Ashish; Ghimire, Rajib; Nepal, Sagar; Gautam, Shasit; KC, Subin; Dhakal, Sudip; Parajuli, Sandeep; Mishra, Anjay Kumar (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2022)
Narayani Lift Irrigation System is one of the oldest lift irrigation systems in Nepal, constructed in 1982. The machines used are as old as the project and, some were maintained and are still in operation. The study focuses on the operation assessment of the Narayani Lift Irrigation System. Field visits with a checklist, a Questionnaire survey, Key informant interviews were the main methods of data collection. The data was analysed using the Relative Importance Index and descriptive statics. The past performance of the system indicates irrigation coverage of only 4,700 Ha of the pump scheme that too with occasional supplements to the Khageri irrigation system in the event of scarcity. Dispute during the water distribution time was frequently observed and the role of NLIWUA was effective in dispute management. The system operation changes were observed in the socio-economic and agricultural status of the users. An increase in the economic status by 45% is noted, 55.4 % of farmers have been motivated towards agriculture. A shift of farmers from rice plantations to cash crops is noted. The operational cost and maintenance cost of components of the pump house were allocated by Government. The budget allocated was sufficient only for the temporary maintenance, but the system needs proper rehabilitation. Sediment Management is the main problem of the system; hence improvement needs to be done. How to cite this article:  Ruwali A, Ghimire R, Nepal S et al. Assessing the Operation Management: A Case of Narayani Lift Irrigation System, Nepal. J Adv Res Geo Sci Rem Sens 2022; 9(3&4): 1-25. DOI:  https://doi.org/10.24321/2455.3190.202201